PATIENT-CENTERED COMMUNICATION dan KOMUNIKASI TERAPEUTIK FISIOTERAPIS DI RS MITRA KELUARGA KENJERAN - Putra, I Putu Krisna (Ilmu Komunikasi, FISIP Universitas Pasundan, 2025)
High motivation and support from the people around them are two of the factors for patients to achieve their recovery. In the context of patient-centered communication, treatment recovery boils down to the patient, and information about the patient's history is also needed to obtain holistic, appropriate, safe, and effective health treatment, patient compliance in taking medication, and suitability for further treatment plans. The relationship and participation between physiotherapists and patients is key in the view of patient-centered communication. Therapeutic communication has an important role that physiotherapists can play to encourage patients to achieve their recovery. This study aims to explore the communication practices carried out by physiotherapists with patients at Mitra Keluarga Kenjeran Hospital, Surabaya. This qualitative research uses a phenomenological approach. Data was collected from physiotherapists and patients through interviews and observations. The research results show that the aim of physiotherapy services is to develop, maintain, and improve body function and movement. Through a structured physiotherapy program, emotional support and good therapeutic communication can increase patient motivation in achieving recovery. With this holistic approach, physiotherapy becomes an integral part of improving and helping to achieve a more significant quality of human life. Apart from that, through patient-centered communication, if the interaction and participation of physiotherapists with patients is carried out well, it can positively influence the quality of health in the short and long term. In patient-centered communication, apart from the goal of healing, other things that can be achieved are related to the perception of the quality of health services and patient satisfaction.